Octaketide Synthase from Polygonum cuspidatum Implements Emodin Biosynthesis in Arabidopsis thaliana. (4th February 2021) - Guo, Yanwu; Nassar, Sara; Ma, Lanqing; Feng, Guanping; Li, Xing; Chen, Mo; Chai, Tuanyao; Abdel-Rahman, Iman A M; Beuerle, Till; Beerhues, Ludger; Wang, Hong; Liu, Benye
Abstract: Plant anthranoids are medicinally used for their purgative properties. Their scaffold was believed to be formed by octaketide synthase (OKS), a member of the superfamily of type III polyketide synthase (PKS) enzymes. Here, a cDNA encoding OKS of Polygonum cuspidatum was isolated using a homology-based cloning strategy. When produced in Escherichia coli, P. cuspidatum octaketide synthase (PcOKS) catalyzed the condensation of eight molecules of malonyl-CoA to yield a mixture of unphysiologically folded aromatic octaketides. However, when the ORF for PcOKS was expressed in Arabidopsis thaliana, the anthranoid emodin was detected in the roots of transgenic lines. No emodin was found in the roots of wild-type A. thaliana . This result indicated that OKS is the key enzyme of plant anthranoids biosynthesis. In addition, the root growth of the transgenic A. thaliana lines was inhibited to an extent that resembled the inhibitory effect of exogenous emodin on the root growth of wild-type A. thaliana . Immunochemical studies of P. cuspidatum plants detected PcOKS mainly in roots and rhizome, in which anthranoids accumulate. Co-incubation of E. coli - produced PcOKS and cell-free extract of wild-type A. thaliana roots did not form a new product, suggesting an alternative, physiological folding of PcOKS and its possible interaction with additional factors needed for anthranoids assembling in transgenic A. thaliana . Thus, transgenic A. thaliana plants producing PcOKS provide an interesting system for elucidating the route of plant anthranoid biosynthesis.